Analysis of Volatile Organic Compounds of Different Types of Peppers (Capsicum annuum L.) Using Comprehensive Two‐Dimensional Gas Chromatography With Time‐of‐Flight Mass Spectrometry - Huixia Zhu; Min Wei; Yuxin Zhang; Xinglin Tao (eFood)
Abstract As a vegetable and spice crop, the quality of pepper (Capsicum annuum L.) is considerably affected by flavor. However, research on flavor of different C. annuum L. varieties, such as the fruits of “Gansu Xianjiao” (GX) and “Gansu Banjiao” (GB), is limited. In this study, comprehensive two‐dimensional gas chromatography with time‐of‐flight mass spectrometry and multivariate statistical analysis were used to elucidate the flavor differences between GX and GB. A total of 2458 volatile organic compounds (VOCs) were identified, with GX and GB possessing 1914 and 1802 VOCs, respectively. Multivariate statistical analysis revealed 215 differential VOCs in GX versus GB. The relative contents of pyrazine, 2‐ethenyl‐6‐methyl and 1‐cyclohexene‐1‐carboxylic acid, 2,6,6‐trimethyl‐, ethyl ester were most significantly increased, whereas those of 4‐methylpentyl 4‐methylpentanoate methional and 2‐furanmethanol,5‐methyl‐ were most significantly decreased. Further, these differential VOCs were correlated with sensory attributes, such as the sweetness, fruitiness, and green aroma. This study will provide deeper insights into improving the flavor quality of C. annuum L.